Intravitreal Anti-Vascular Endothelial Growth Factor Agents for the Treatment of Diabetic Retinopathy: A Review of the Literature - Irini Chatziralli; Anat Loewenstein (MDPI AG, 2021)
Background: Diabetic retinopathy (DR) is the leading cause of blindness in the working-age population. The purpose of this review is to gather the existing literature regarding the use of the approved anti-vascular endothelial growth (anti-VEGF) agents in the treatment of DR. Methods: A comprehensive literature review in PubMed engine search was performed for articles written in English language up to 1 July 2021, using the keywords "diabetic retinopathy", "ranibizumab", "aflibercept", and "anti-VEGF". Emphasis was given on pivotal trials and recent robust studies. Results: Intravitreal anti-VEGF agents have been found to significantly improve visual acuity and reduce retinal thickness in patients with diabetic macular edema (DME) in a long-term follow-up ranging from 1 to 5 years and are considered the standard-of-care in such patients. Regarding DR, intravitreal anti-VEGF agents provided ≥2-step improvement in DR severity on color fundus photography in about 30-35% of patients with NPDR at baseline, in the majority of clinical trials originally designed to evaluate the efficacy of intravitreal anti-VEGF agents in patients with DME. Protocol S and CLARITY study have firstly reported that intravitreal anti-VEGF agents are non-inferior to panretinal photocoagulation (PRP) in patients with proliferative DR (PDR). However, the use of new imaging modalities, such as optical coherence tomography-angiography and wide-field fluorescein angiography, reveals conflicting results about the impact of anti-VEGF agents on the regression of retinal non-perfusion in patients with DR. Furthermore, one should consider the high "loss to follow-up" rate and its devastating consequences especially in patients with PDR, when deciding to treat the latter with intravitreal anti-VEGF agents alone compared to PRP. In patients with PDR, combination of treatment of intravitreal anti-VEGF agents and PRP has been also supported. Moreover, in the specific case of vitreous hemorrhage or tractional retinal detachment as complications of PDR, intravitreal anti-VEGF agents have been found to be beneficial as an adjunct to pars plana vitrectomy (PPV), most commonly given 3-7 days before PPV, offering reduction in the recurrence of vitreous hemorrhage. Conclusions: There is no general consensus regarding the use of intravitreal anti-VEGF agents in patients with DR. Although anti-VEGF agents are the gold standard in the treatment of DME and seem to improve DR severity, challenges in their use exist and should be taken into account in the decision of treatment, based on an individualized approach.